Novel formulation for co-delivery of cinnamon- and cumin-loaded polymeric nanoparticles to enhance their oral bioavailability - Aditi Sangal (17788523) (2023)
Nanobiotechnology has been an encouraging approach to improving the efficacy of hydrophobic bioactive compounds. The biologically active constituents present in herbal extracts are poorly absorbed, resulting in loss of bioavailability and efficacy. Hence, herbal medicine and nanotechnology are combined to overcome these limitations. The surface-to-volume ratio of nanoparticles is high and as the size is small, the functional properties are enhanced. The present study reports the synthesis of cinnamon and cumin (Ci–Cu) dual drug-loaded poly (D, L-lactide-co-glycolide) (PLGA) nanoparticles (NPs) to overcome the limitations of oral bioavailability and extend the effect of these drugs for alleviating health problems. The solvent evaporation method was adopted for the synthesis, and the as-prepared nanoparticles were characterized by Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, Transmission electron microscopy (TEM) and X-ray diffraction (XRD). The average size of the formed spherical Ci-Cu nanoparticles ranged between 90 and 120 nm. The encapsulation efficiency of the drug was found to be 79% ± 4.5%. XRD analysis demonstrated that cinnamon and cumin were amorphously scattered in the PLGA matrix. The FTIR bands showed no evident changes suggesting the no direct molecular interactions between the drug and the polymer. At pH 6.9, the release studies in vitro exhibited a burst initially followed by a tendency to obtain a slower steady release. The results indicated that the Cu-Ci dual drug-loaded polymeric NPs has drug release at a slower rate. The time taken for 25% release of drug in Ci-Cu-loaded PLGA NPs was twice as compared to cumin-loaded PLGA Nps, and three times compared to cinnamon-loaded PLGA NPs. Other Information Published in: 3 Biotech License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13205-023-03480-8